Making Chosŏn's Own Tributaries : Dynamics between the Ming-centered World Order and a Chosŏn-centered Regional Order in the East Asian Periphery - 정다함 (International journal of Korean history, 2010)
Kyŏngcha’gwan, conventionally known as Chosŏn kings’ domestic envoys, were the envoys who also delivered the Chosŏn kings’ orders to their vassals such as the Jurchens and Tsushima. This fundamental characteristic of Kyŏngcha’gwan culminated in the ceremonial rituals of receiving Kyŏngcha’gwan, which signified Chosŏn’s “lesser suzerainty” over its vassal, under the bigger umbrella of Ming “suzerainty.” The reason why these vertical dimensions of Chosŏn-Jurchen and Chosŏn-Tsushima relations in 15th century have not been scrutinized actually lies in the “Kyorin” frame, which was modern invention of the same term in modern Korean historiography. “Kyorin” as a modern frame implies that Chosŏn tried to maintain peaceful relations with the Jurchens and Tsushima, based on its Confucian orientation. Korean historians could not conceptualize what did not fit in that frame,because they were too overwhelmed by traditional “Sino-centric” perspective to provincialize and de-centralize it, on the one hand. And they were also stuck in the mythology of a peace-loving and innocent Korea produced by their single lineal evolutionary frame of “Korean History (Hanguksa)” which is based on the hereditary victimhood of modern Korean historiography, on the other hand. With their eyes blinded, it was unable for them to provincialize both the “Sino-centric”and “Korea-centered” perspectives, they were not able to re-conceptualize the various active dimensions of regional dynamics that constituted Chosŏn-Jurchen and Chosŏn-Tsushima relations in 15th century. Furthermore, the nature and logic of the Kyorin frame, which argued that early Chosŏn’s advanced cultures helped the Jurchen and Tsushima to be more civilized and which have deliberately downplayed early Chosŏn’s expansionist military and interstate policies toward the Jurchens and Tsushima, ironically takes exactly after the nature and logic of Japanese Imperialist’justifications of the colonization of Chosŏn, which Korean scholars have continued to reject up to the present. In fact, the historical origin of this regional hierarchy where Chosŏn was able to force this practice on Jurchens and Tsushima was not something just mainly “cultural.” Rather, it was Koryŏ and Chosŏn’s military subjugation of them and Chosŏn’s founder Yi Sŏng’gye’s contribution to it. According to the changes in the East Asian interstate frame, the ruling elites of early Chosŏn used these subjugations as useful historical sources for legitimizing their superiority over those two non-Chosŏn polities in writing its own history. Through this, the ideological basis of Chosŏn’s having its own vassals such as the Jurchen and Tsushima was created. And on the basis of this idea, Chosŏn’s ruling elites tried to perpetuate their imagined “suzerainty” over them. The dispatch of Kyŏngcha’gwan was one of the typical diplomatic practices to symbolize this relationship. The institutional origins of Kyŏngcha’gwan shed light on this symbolic meaning of Chosŏn’s Kyŏngcha’gwan more clearly. Ming sent its low-level envoys called Qinchaiguan (欽差官) to its vassals such as Chosŏn. Imitating the Ming’s imperial mode of interstate policies, Chosŏn came up with Chosŏn’s own version of Ming imperial model, such as Kyŏngcha’gwan (敬差官) dispatches to the Jurchens and Tsushima that Chosŏn identified as its vassals. However, this does not necessarily mean that Chosŏn denied the “Sino-centric” East Asian order. Rather, by modifying its original imperial model according to Chosŏn’s own position under Ming, Chosŏn could still signify its suzerainty over the Jurchen and Tsushima, without violating Ming suzerainty. Chosŏn’s ruling elites who carried out interstate policy in 15th century were very shrewd, aggressive, and even mean. Was Chosŏn ruling elites’superiority to the Jurchens and Tsushima only “cultural” as t... KCI Citation Count: 5